PATIENTS WHO ATTEND FORMAL PHYSICAL THERAPY FOR THE ENTIRE DURATION OF RECOVERY AFTER ACLR DEMONSTRATE EXCELLENT FUNCTIONAL OUTCOMES. Issue 7 (30th July 2021) - Link, Meredith; Greenberg, Elliot
Background: Limitations in insurance coverage and higher out-of-pocket expenses create challenges for physical therapists rehabilitating pediatric athletes after anterior cruciate ligament reconstruction (ACLR). While recovery may last 9-12 months, rehabilitation typically lasts <7 months. Unfortunately, research indicates many pediatric athletes have poor functional performance at the time of returning to sports. This may indicate incomplete rehabilitation within our current model of treatment. Understanding how rehabilitation utilization relates to functional outcomes may help optimize physical therapy (PT) treatment for pediatric patients post-ACLR. Purpose: To report the pattern of visit usage and functional outcomes of ACLR patients who were cared for within a large, pediatric specialty care network. Methods: A retrospective study of ACLR patients ≤18 years-old who underwent surgery between December 2016 and August 2019. All subjects must have completed rehabilitation within the sponsoring institutions PT centers and completed a functional hop testing battery, consisting of four single leg hop tests, prior to 10 months post-operative. The frequency of subjects able to achieve ≥90% limb symmetry (LS) on all hop tests was calculated and served as the main outcome of interest. Results: Out of 120 potential subjects, 53 were excluded for missing data, treatment at other facilities or care extending outside the designated time-frame, leaving 67 subjects (mean age 14.6 ± 1.5 SD, 38% female) for analysis. On average, PT began 14 days (range 5-33) post-operatively and subjects attended a mean of 40 visits (range 16-64) throughout 9 months of rehabilitation. The mean (range) number of sessions attended during rehabilitation was as follows: 0-6 weeks: 6 sessions (1-12), 7-12 weeks 10 sessions (2-15), 3 to 6 months 14 sessions (1-25), 6 to 9 months 9 sessions (0-23). Hop testing was completed 8 months post-surgery (range 5-10) with 85% of subjects achieving >90% LS on all tests. Conclusion: Physical therapy at a pediatric specialized center resulted in superior functional performance compared to existing literature. Interestingly, visit frequency was maintained throughout a 9-month period, which is not typical practice. Treatment during this latter phase of rehabilitation, involves advanced plyometric and sports conditioning, which may explain the high level of performance seen. Sampling bias and limitations is sample size, warrant caution in interpreting these results; however this data demonstrates that PT within a specialized setting, encompassing the entire duration of recovery after ACLR, yields excellent functional outcomes. Future investigations, within a larger and diverse sample are necessary to more fully understand these factors.